Development of the TIP-HOLE gas avalanche structure for nuclear physics/astrophysics applications with radioactive isotope beams: preliminary results. (April 2020) - Randhawa, J.S.; Cortesi, M.; Mittig, W.; Wierzbicki, T.; Gomez, A.
Abstract: We discuss the operational principle and performance of new micro-pattern gaseous detectors based on the multi-layer Thick Gaseous Electron Multiplier (M-THGEM) concept coupled to a needle-like anode. The new gas avalanche structure aims at high-gain operation in nuclear physics and nuclear astrophysics applications with radioactive isotope beams. It is thereafter named TIP-HOLE gas amplifier, and consists of a THGEM or a two-layers M-THGEM mounted in a WELL configuration. The avalanche electrodes are collected by thin conductive needles (with up to a few ten μm radius and a height of 100 μm), located at the center of the hole and acting as a point-like anode. The bottom area of the needle could be surrounded by a cylindrical cathode strip in order to increase the electron collection efficiency. The electric field lines from the drift region above the M-THGEM are focused into the holes, and then forced to converge on the needle tip. An extremely high field is reached at the top of the needle, creating a point-like avalanche process. Stable, high-gain operations in a wide range of pressures can be achieved at relatively low operational voltage, even in pure quencher gas at atmospheric pressure (e.g. pure isobutene). The TIP-HOLE structure may be produced by the innovative scalable additive manufacturing technology for large-area, multiple-layer printed circuit boards, recently developed by the UHV technology company (USA) and discussed for the first time in this work.